Analysis of Flavonoids and Saponins of Contents in the Ration of Sheep Added with Multinutrient Block with Different Level of Papaya Leaves Flour - A. Arumsari; S. Mukodiningsih; Widiyanto Widiyanto (Universitas Bengkulu, 2021)
This study aimed to examine the composition of flavonoids and saponins in sheep rations added with multi-nutrient blocks with different levels of papaya leaves (0%, 2%, 4%, and 6%). The research design used was a completely randomized design with 4 treatments and 3 replications. The treatment used was T0: sheep ration added MNB without papaya leaves flour, T1: sheep ration added MNB using 2% papaya leaves flour, T2: sheep ration added MNB using 4% papaya leaves flour, and T3: sheep ration added MNB using 6% papaya leaves flour. The parameters reviewed were flavonoids and saponins. The materials used were sheep ration (forage and concentrate), multi-nutrient blocks and papaya leaves flour. The method used is making complete rations, making MNB, and the analysis stage. The treatment used in the study was a complete ration, consisting of forage and concentrate added with multi-nutrient blocks with papaya leaf levels of 0%, 2%, 4%, and 6%. The results of the study were that sheep ration added MNB with different levels of papaya leaves flour did not show an increase in flavonoids and saponins. The highest flavonoids content was found at sheep ration added MNB using 4% papaya leaves flour while the highest saponin content was found at sheep ration added MNB using 6% papaya leaves flour.